2013
DOI: 10.3109/0886022x.2013.801271
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of high-density lipoproteins are associated with acute kidney injury following revascularization for chronic limb ischemia

Abstract: .001) were independently associated with increased odds for developing AKI. Propensity score analyses showed low HDL was independently associated with increased odds of AKI (OR 2.4 (1.4-4.2)). Conclusions: AKI following revascularization is not uncommon (12.0%), and lower concentrations of HDL and serum albumin are associated with increased odds of postoperative AKI. There was also a trend of higher prevalence of AKI among those with pre-existing CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
17
2
Order By: Relevance
“…In addition, over 40% of patients were excluded in the BCBS analysis due to missing serum creatinine levels postintervention—and therefore cases of AKI may have not been captured. Of note, the present mean incidence of 10.4% is also comparable to smaller studies that included a significant proportion of CLI patients …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, over 40% of patients were excluded in the BCBS analysis due to missing serum creatinine levels postintervention—and therefore cases of AKI may have not been captured. Of note, the present mean incidence of 10.4% is also comparable to smaller studies that included a significant proportion of CLI patients …”
Section: Discussionsupporting
confidence: 85%
“…Of note, the present mean incidence of 10.4% is also comparable to smaller studies that included a significant proportion of CLI patients. 16,17 The temporal trend of AKI incidence suggests that despite increased awareness and published data, this complication is growing in frequency and is of clinical significance. The rise in comorbidity prevalence over the analysis period appears to be a key contributor.…”
Section: Aki Rates In Peripheral Angiography and Endovascular Therapymentioning
confidence: 99%
“…After removal of duplicates and nonrelevant articles, 50 potentially relevant studies were identified and ultimately 20 studies were selected that included data on patients undergoing peripheral angiography or interventions. These 20 studies were then analyzed in detail and separated into those with ( n = 15) (Table ) and without ( n = 5) granular data regarding lower extremity peripheral angiography related AKI incidence . The aggregate median data from the 15 studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The rates of reported AKI varied amongst the 15 studies, ranging from 0 to 45%, with a median of 10.0% and an average of 11.2% ± 10.0%. The 7 studies with at least 200 procedures had an average incidence of 9.3% ± 2.3% and median incidence of 10.0% . The incidence of AKI in the overall study cohort is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation